2021
DOI: 10.47577/tssj.v22i1.4330
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Service Marketing Mix and Umrah Service Quality on Customer Satisfaction and Customer Loyalty towards Umrah Travel Agents in Malaysia

Abstract: In the Malaysian Umrah industry, there are so many new participants selling and offering similar products and services. As a result, Umrah providers must compete to survive in this industry, as there are currently so many competitors.  They need to focus on customers’ special needs and preferences to maintain and retain the long-term relationship. Thus, the objective of this study is to examine the relationship between service marketing mix and Umrah service quality on customer loyalty towards Umrah travel age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…Do and Vu [38] underlined the importance of pricing in customer choices and satisfaction in the Vietnamese railway industry. Al-Sukar and Alabboodi's [65] research in Jordan and Othman et al's [69] study in the Umrah Travelling Industry in Malaysia discovered statistically significant connections between the e-marketing mix (price) and consumer satisfaction. Nasib [66] used customer satisfaction at Binjai Hypermart in Indonesia to show how pricing has a favourable and substantial relationship with customer loyalty.…”
Section: -The Relationship Between E-pricing and Customer Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Do and Vu [38] underlined the importance of pricing in customer choices and satisfaction in the Vietnamese railway industry. Al-Sukar and Alabboodi's [65] research in Jordan and Othman et al's [69] study in the Umrah Travelling Industry in Malaysia discovered statistically significant connections between the e-marketing mix (price) and consumer satisfaction. Nasib [66] used customer satisfaction at Binjai Hypermart in Indonesia to show how pricing has a favourable and substantial relationship with customer loyalty.…”
Section: -The Relationship Between E-pricing and Customer Satisfactionmentioning
confidence: 99%
“…Muhaimin and Yapanto [70] showed the relationship between e-place and purchases in Indonesia. Othman et al [69] found a significant effect between service marketing mix (place) and customer satisfaction in the Umrah Traveling Industry in Malaysia. Saidani and Sudiarditha [55] highlighted the positive effect of distribution on consumer satisfaction in Jakarta, emphasising the importance of smooth distribution for enhanced satisfaction.…”
Section: -The Relationship Between E-place and Customer Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modality and content of training programs are evolving, encompassing traditional face-to-face learning, and leveraging technology to offer flexible, customized, and interactive e-learning solutions (Salas, Tannenbaum, Kraiger, & Smith-Jentsch, 2012). A blend of learning approaches ensures that training caters to diverse learning needs, styles, and paces, enhancing the learning experience and outcomes (Othman et al, 2020).…”
Section: Trainingmentioning
confidence: 99%
“…The conventional technique of teaching and learning in the classroom, in which both the teacher and the learner must be physically present in the same room , was used in the past . This is still the most prevalent technique of instruction, and it is used all around the world (Othman et al, 2020). However, internet technology appears to have rendered the traditional method of teaching obsolete (Majeed et al, 2021), and a number of academics have proposed that education through the use of information and communication technology tools, learning is defined as the practice of teaching and learning through the use of electronic equipment (Jamal, 2021), such as computers to view interactive learning films, electronic whiteboards for teaching, photo and video editing, and the use of sound during a presentation (Ismeal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%